Scrotal Abscess Drained by Iatrogenic Urethral Fistula in an Adult Diabetic Male - Marco Stizzo; Davide Arcaniolo; Carmelo Quattrone; Raffaele Balsamo; Marco Terribile; Celeste Manfredi; Vincenzo Mirone; Paolo Verze; Marco De Sio (Case Reports in Urology)
A 46-year-old Caucasian male has been transferred to our urology department with a history of septic fever, uncompensated diabetes, pain, and scrotal swelling. On clinical examination, the left inguinal and scrotal area was swollen, tender, and painful; scrotal MR had been performed, showing the catheter tip in scrotal cavity and presence of gas. The case was diagnosed as scrotal abscess with urethroscrotal fistula. He was successfully treated with scrotal incision, drainage, catheter repositioning under fluoroscopic control, antibiotics, and insulin. This patient developed an infection of scrotum, which led to subcutaneous abscess getting worse by a poorly controlled glycemia. In this case, an iatrogenic fistula, caused by wrong catheterization, stops the evolving to a Fournier’s Gangrene. Early detection and intervention provide opportunities to improve outcome of this disease.